GENETIC POLYMORPHISM AND CYTOGENETIC CHANGES IN THE PERIPHERAL BLOOD T-LYMPHOCYTES OF PATIENTS WITH ARTHRITIS ASSOCIATED WITH IXODES TICK-BORNE BORRELIOSIS IN THE NORTHERN REGIONS OF SIBERIA - N. N. Ilyinskikh; E. N. Ilyinskikh; V. P. Zuevsky; A. G. Semenov (Научно-практическая ревматология)
The authors have previously conducted studies that demonstrate the increased level of cytogenetic disturbances in patients with Ixodes tick-borne borreliosis (ITB). The severity of arthritis associated with ITB (AITB) is also ascertained to depend on whether the patient has certain HLA-DRB1 alleles.Objective: to assess the association between HLA-DRB1 gene polymorphism and cytogenetic changes in the peripheral blood T lymphocytes of patients with AITB.Subjects and methods. 146 patients with AITB, 100 clinically healthy convalescents with ITB (CITB), and a control group of 98 healthy blood donors (HBDs) without a history of tick-borne infections were examined using cytogenetic (micronucleus analysis of cytokinesis-blocked peripheral blood T lymphocytes) and molecular genetic (PCR analysis of HLA-DRB1 gene polymorphism) methods.Results and discussion. The frequency of cytokinesis-blocked lymphocytes with micronuclei in the AITB group was significantly higher than that in the CITB and HBD groups (p<0.01) with the exception of the results obtained in the subgroup of patients with AITB who had the DRB1*10 allele (p>0.05). The highest levels of lymphocytes with micronuclei were observed in AITB patients with the DRB1*17(03), *01, and *04 alleles as compared to those in the CITB and HBD groups (p<0.001). The CITB group showed the most significant increase in the detection rate of lymphocytes with micronuclei in people with the DRB1*01, DRB1*04, or *17(03) alleles. At the same time, there were no significant differences in the number of lymphocytes with micronuclei in the HBD group, depending on the HLA-DRB1 gene alleles (p>0.05). Thus, the patients with AITB had the highest frequency of cytogenetic disorders with the exception of individuals with the DRB1*10 allele.